A human-centered designed outreach strategy for a youth contraception navigator program - Tracey A. Wilkinson; Bridget Hawryluk; Courtney Moore; Jeffrey F. Peipert; Aaron E. Carroll; Sarah Wiehe; J. Dennis Fortenberry (Elsevier, 2022)
Objective: To identify key elements of an outreach strategy for a youth contraception navigator program designed to help young people overcome barriers to contraception access. Methods: A human-centered design approach was used to engage adolescents aged 15-17 in co-design sessions. Human-centered design techniques, such as affinity diagramming and model building were used to inform key elements of the communication model and the final outreach strategy messages. Results: Messages focused on the individual, normalizing talking about birth control, acknowledging the challenges to obtaining birth control, explaining how the navigator program works resonate with young people. Having images of diverse participants, offering information about birth control, and showing images of reputable sources will enhance trust. Conclusions: A name (IN Control) and key elements of an outreach strategy were determined for the navigator program. It is important to work with key stakeholders and co-design the optimal strategy and messages to assure that the intended audience is reached, and the desired behavior change is achieved. Innovation: Human-centered design techniques can be used to provide insight into programmatic outreach strategies for a contraception navigator program to increase their impact and ultimate success.